Efektivitas Sistem Pengelolaan Irigasi Ramah Lingkungan melalui Optimalisasi Pola Tanam di DAS Wedoro Pasuruan - Eko Cahyo, Mulyanto; Maulidiyah, Afrikhatul (Jurnal Civil Engineering Study, 2025)
This study aims to evaluate the effectiveness and efficiency of the irrigation management system in the Wedoro Irrigation Area, Pandaan District, Pasuruan Regency, and to examine its impact on environmental sustainability. The research employed a descriptive quantitative approach through water discharge measurements, crop water requirement analysis, and cropping pattern simulations based on water balance. Results show that water distribution efficiency reached only 42.90%, while the network effectiveness was 87.63%, both below ideal standards. The cropping pattern simulation indicated that the Rice–Maize–Soybean combination was more adaptive to water availability and environmentally friendly. Low efficiency was mainly caused by leakage and sedimentation in the canals, which also led to groundwater exploitation and environmental degradation. Canal normalization and enhanced farmer participation in irrigation management are necessary. These findings highlight the importance of integrating irrigation management with environmental protection efforts to support sustainable agriculture.